The Attitude of Work-Oriented and Family-Oriented Chinese Women Toward the Evaluations Based on the Traditional Positive Stereotype That Women Are Virtuous - Song, Jingjing; Li, Junnan; Liu, Yanfen; Ruan, Yifan (Frontiers in Psychology, 2021)
People typically reject being negatively stereotyped but overlook the ways in which they are positively stereotyped. The current study focused on the attitude of Chinese women toward being evaluated based on the traditional positive stereotype that women are virtuous; family/work centrality as a boundary condition of these attitudes; and three perceptions that may mediate the link between this type of evaluation and attitudes of women. In experiment 1, female college students were identified as work-oriented or family-oriented based on their responses to a questionnaire regarding their focus on these two domains. They then read a vignette in which a man evaluated a female target under random assignment to one of three conditions, namely: group positive stereotype evaluation, individual positive stereotype evaluation, or unstereotypical positive evaluation. The participants rated how much they liked the female target, as an indicator of their attitude toward evaluations based on the stereotype that women are virtuous. In experiment 2, female college students were classified as work- oriented or family-oriented, and then read a vignette in which a man (the target) evaluated them. They were randomly assigned to the group positive stereotype evaluation, individual positive stereotype evaluation, or unstereotypical positive evaluation. Participants rated how much they liked the male target, as an indicator of their attitude toward evaluations based on the positive stereotype that women are virtuous. Across both studies, ANOVA showed that work-oriented women liked evaluations based on both group and individual stereotypes less than the family-oriented women. Regression-based analyses showed evidence of a mediation process in which work-oriented women viewed the virtuous positive stereotype as implying a prescriptive social demand that women should engage in family roles, resulting in a negative reaction to this type of evaluation.